2021
DOI: 10.2503/hortj.utd-263
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Yield Components and the Relationship Between Dry Matter Production and Fruit Yield in Greenhouse Sweet Pepper (<i>Capsicum annuum</i>)

Abstract: To improve the yield of sweet peppers in Japan, we investigated the relationships between plant growth characteristics and fruit yield, with a particular focus on dry matter production. Fruit fresh weight (i.e., fruit yield) was highly correlated with fruit dry weight. Aboveground dry matter production was correlated with both light use efficiency and intercepted photosynthetically active radiation. Although the number of fruits was correlated with the fruit set ratio, no correlation was found between the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Therefore, during this experiment, we could calculate the fruit sink strength without considering the seasonal variation of the fruit weight. Crop parameters for estimating TDM m_st [IL m (k), LUE m (a and o)] have statistical validity according to Watabe et al (2021). During this study, we used TDM m_st calculated using these crop parameters, but there were differences between the observed and calculated TDM m_st at 84 and 118 DAT (observed TDM m_st > calculated TDM m_st ); these differences decreased after 118 DAT (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, during this experiment, we could calculate the fruit sink strength without considering the seasonal variation of the fruit weight. Crop parameters for estimating TDM m_st [IL m (k), LUE m (a and o)] have statistical validity according to Watabe et al (2021). During this study, we used TDM m_st calculated using these crop parameters, but there were differences between the observed and calculated TDM m_st at 84 and 118 DAT (observed TDM m_st > calculated TDM m_st ); these differences decreased after 118 DAT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By using models of dry matter production (Higashide, 2018(Higashide, , 2022Watabe et al, 2021) and fruit growth based on Eqs. [5] and [6], we investigated the quantitative conditions associated with fruit set and abortion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were conducted in a greenhouse compartment (width: 18 m, length: 18 m, gutter height: 5 m) at the Institute of Vegetable and Floriculture Science, National Agriculture and Food Research Organization, Tsukuba, Japan (36°26′N, 140°10′E). Commercial sweet pepper (Capsicum annuum L. 'Artega') (Enza Zaden, Enkhuizen, The Netherlands) was grown hydroponically using a rockwool system, as previously described (Watabe et al 2021).…”
Section: Growth Conditionsmentioning
confidence: 99%
“…There are no tools for predicting growth and yield based on dry matter production in sweet pepper, although several studies have presented yield prediction models using artificial neural network-based trend analyses of environment, plant age, and yield (Lin & Hill 2008;Lin et al 2009;Al-Halimi & Moussa 2015). In a previous study on sweet pepper, we evaluated the relationship between yield and its components (Watabe et al 2021). As in tomatoes, comprehensive analyses of correlation among the yield components showed that sweet pepper yield could also be determined from the hierarchical structure of total dry matter production -there was a strong correlation among fruit fresh weight and fruit dry weight, total dry matter production, and light use efficiency.…”
mentioning
confidence: 99%